Quantitative analysis of the flight calls and trills of Evening Grosbeaks (Coccothraustes vespertinus) - Kirsch, William M.; Centanni, Caleb T.; Ngo, Song Han; Young, Matthew A.; Hahn, Thomas P.; Robinson, W. Douglas (Frontiers in Bird Science, 2025)
Diversity within species can be masked by minor differences in external appearance but revealed by group differences in vocal characteristics such as flight calls of Fringillid finches. These flight calls vary among infraspecific groups within a species. In Evening Grosbeaks (Coccothraustes vespertinus), existence of five distinct call types have been hypothesized to occur, yet the variation within and between the different call types has yet to be quantitatively evaluated. We measured characteristics of flight calls and another common call form, trills, across the North American range of the Evening Grosbeak. We analyzed our own recordings as well as those contributed to digital sound archives to map, measure and, with the aid of cluster and discriminant function analyses, classify flight calls and trills into types. Flight calls of types 1, 2, 3, and 4 were readily distinguishable from each other but trills were less distinctive. A fifth set of calls that group together in cluster analyses includes birds from the southwestern United States, Mexico and, surprisingly, from Alberta and Saskatchewan, Canada. However, flight calls from central Canada and Mexico/Arizona still showed several statistically significant differences, so we hypothesize existence of six flight call types. Our interpretation may be influenced by currently small sample sizes and lack of summer samples from Mexico. Here, we refer to the Mexico/Arizona birds as type 5 and the Alberta and Saskatchewan birds as type 6 but recognize that additional information could provide stronger evaluation of these categories. Except for some type 3, 4 and 6 flight calls that were very similar according to the spectrographic properties included in our analyses, most Evening Grosbeak flight calls are diagnosable to type with a high degree of confidence. We encourage additional collection of recordings across North America, especially from central Canada, Arizona, and Mexico. Future studies can utilize sound recordings to identify infraspecific call type groups, map their seasonal movements and investigate variation in call structure through time to facilitate progress toward unraveling the evolutionary importance of such cryptic diversity.